The incremental information content of AC 201 inflation-adjusted data - D. P. Du Plessis; A. A. Archer; J. F. Affleck-Graves (South African Journal of Business Management, 1986)
In this article an attempt is made to examine the extent to which inflation-adjusted income figures (derived from AC 201 data) contain information not included in the historic figures currently reported. The usefulness (or information content) criterion is examined from the aggregate market perspective through an empirical examination structured to determine which set of figures best represents the information impounded in share prices. The research design incorporates a two-stage regression approach which permits a determination of the incremental explanatory power of collinear variables. The results obtained suggest that there are information content differences between inflation-adjusted and historic data as measured through the association with share returns. Only for those companies affected to a lesser extent by the effects of inflation could no discernable difference in information content be detected. Bar this exception, the results appear to support the hypothesis that inflation-adjusted data contain information that is on aggregate not reflected in the financial reports currently produced. However, the contention that historic income also possesses information beyond that provided by inflation-adjusted income is not supported by the results. The research findings have important implications for reporting policy in SA regarding the future of inflation accounting requirements and seem to suggest that the SA Institute of Chartered Accountants should seriously consider making a form of inflation accounting mandatory.
Keywords: 650